Assessment of Outcome of Surgery in Patients with Primary Hyperparathyroidism - Harmeet Pal Singh Dhooria; Rishab Garg; Parminder Singh; Ravinder Pal Singh (Asian Journal of Medical Research, 2019)
Background: Parathyroid hormone (PTH) mobilizes calcium by increasing calcium resorption from bone and by raising calcium reabsorption in the proximal kidney tubule. Primary hyperparathyroidism (PHP) results from inappropriate overproduction of parathyroid hormone from one or many parathyroid glands and presents with hypercalcemia. In the surgical management of PHP intraoperative PTH (IO-PTH) assays have been shown to improve the success of parathyroid gland surgery. Minimally invasive parathyroidectomy (MIP) has replaced the traditional four-gland bilateral exploration as the procedure preferred by many institutions. Hence; the present study was undertaken for assessing the outcome of surgery in patients with PHP.Subjects and Methods:The present study included assessment of outcome of surgery in patients with PHP.  Once the suspicious parathyroid was identified, careful dissection with blunt instruments was done to free gland from surrounding fascia. Bipolar was used to ligate the vascular supply and the specimen was removed.  Patients with above mentioned inclusion criteria underwent preoperative localization with USG neck and technetium Tc-99m (99mTc) Sestamibi scan (CT/ MRI Neck when required). Based on results of MIBI and USG neck, the findings were defined as concordant and discordant. Patients with concordant findings of USG neck and Sestamibi scan underwent MIP.  All the results were summarized in Microsoft excel sheet and were analyzed by SPSS software.Results:CT/MRI was done in only 4 patients where 50% of the patients showed involvement of right superior and inferior glands. Minimal invasive parathyroidectomy (MIP) was done in 95.2% patients (20/21) while bilateral neck exploration (BNE) was done in only 1 case of multiple adenoma. The USG neck (n=20) was able to accurately localize abnormal parathyroid glands in 17 patients (85%).Conclusion: In patients undergoing surgical treatment for PHP, Minimal Invasive Parathyroidectomy has excellent prognosis.